EFL Student’s Anxiety in Speaking English - Riski Putri Arimbi; Indri Wirahmi Bay; Fahria Malabar (TRANSBAHASA, 2022)
The present study intends to investigate the factors that affect students’ anxiety in speaking English and the strategies that students use to cope with their anxiety in speaking English. The data of the study were obtained by using mix method. The participants were students of the English Department. Research data were collected by giving questionnaires and interviewing the students. The findings reveal the result that most of the students in the English Department felt anxiety in speaking English. However, most of the students used the strategies to cope with the anxiety while speaking English.